Financial Management Training for Micro, Small, and Medium Enterprises (MSMEs) - Muslim Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to explore the dynamics of financial management training for Micro, Small, and Medium Enterprises (MSMEs), focusing on training trends, approaches used, the suitability of materials to participants' needs, and their impact on business capacity and sustainability. The study also emphasizes the role of technology and identifies challenges and gaps in training implementation. Research Design and Methodology: This study uses a qualitative approach with the Systematic Literature Review (SLR) method. The analysis was conducted on scientific publications over the past ten years that discuss financial management training for MSMEs, identifying common themes, training approaches, and technology integration. Findings and Discussion: The results of the study show that training has shifted from a generic model to a contextual and specific approach. The most relevant training materials include simple financial record-keeping, cash management, the separation of personal and business finances, and basic taxation. Technologies such as digital accounting applications and e-learning enhance training effectiveness, although challenges related to digital literacy remain high. Training also increases confidence, access to financing, and more orderly financial practices. Implications: This research contributes to the development of needs-based, participatory, and sustainable training designs. In practical terms, the results can be used by the government, NGOs, and financial institutions to design more effective and MSME-specific financial training.